PENINGKATAN PRODUKTIVITAS MELALUI IMPLEMENTASI MANAJEMEN USAHA KECIL KULINER AYAM ORIENTAL SAUCE HOMEMADE JEMBER - Intan Nurul Awwaliyah; Gusti Ayu Wulandari; Markus Apriono (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The increasing public interest in processed chicken cuisine in Jember Regency encourages an increased number of chicken cuisine entrepreneurs with various spices and flavors. One of these processed chicken culinary businesses is Ayam Oriental Sauce Homemade Jember. This culinary business was pioneered at the beginning of the 2020 pandemic by offering processed Korean. Due to limited capital, equipment, and labor, products are made of order. Capital limitations lead to a lack of production capacity; Chicken Oriental Sauce Homemade currently lacks the marketing knowledge to remain competitive. The marketing is still limited to neighbors and close friends. Business partners do not yet have a dedicated social network for product marketing and promotion. In addition, business and family finances are still related because partners lack the knowledge and skills to compile simple financial statements. Through the mentoring activities carried out, it is expected that this culinary Mitra will be able to integrate into the business through service activities in the form of management support and business development, resulting in quantitative and qualitative improvement of culinary chicken products.  With the increased knowledge and skills of marketing partners, including product packaging and online promotion through social media, wider marketing reach and higher product sales will be achieved, improving partner well-being